Long-Term Intravitreal Ranibizumab as a Potential Additional Risk Factor for Neurodegeneration in Parkinson’s Disease: A Case Report - Trifirò, Gianluca; Marcianò, Ilaria; Cutroneo, Paola M.; Spina, Edoardo; Mirabelli, Eliana; Trombetta, Costantino J.; Morgante, Francesca (Frontiers in Pharmacology, 2018)
In November 2012, a 72-year old patient was diagnosed with left eye wet age-related macular degeneration. The patient received three monthly intravitreal injections of ranibizumab, with complete resolution of retinal haemorrhage and oedema and reinstatement of visual acuity. In May 2015, symptomatic relapse was detected. The patient was again treated with intravitreal ranibizumab, with overall 6 injections till the end of February 2016. In May 2016, the patient complained left hand resting tremor, bradykinesia and postural rigidity of head and trunk. A diagnosis of clinically established PD was made based on new criteria of the Movement Disorders Society. Single Photon Emission Computerized Tomography of the Dopamine Transporter with 123I-ioflupane, documented a low DAT uptake mostly in the right striatum. Due to the documented protective role of vascular endothelial growth factor (VEGF) on the dopaminergic neurons, intensive intravitreal injections of the anti-VEGF agent ranibizumab may have played as an additional risk factor accelerating the neurodegeneration process related to PD and the onset of the related clinical signs and symptoms.